2017
DOI: 10.1155/2017/3946706
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Cordycepin on D-Galactosamine/Lipopolysaccharide-Induced Acute Liver Injury

Abstract: As the major active ingredient of Cordyceps militaris, cordycepin (3′-deoxyadenosine) has been well documented to alleviate inflammation and oxidative stress both in vitro and in vivo. To explore the potential protective effect of cordycepin in fulminant hepatic failure, mice were pretreated with cordycepin for 3 weeks followed by D-galactosamine (GalN)/lipopolysaccharide (LPS) injection. Then we found cordycepin (200 mg/kg) administration elevated survival rate, improved liver function, and suppressed hepatoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…D-gal can cause liver cell necrosis and lead to ALF, as well as abnormally elevated serum TNF-α, which then triggers the cascade of inflammatory mediators and is closely related to the pathophysiology of ALF[ 28 , 29 ]. In our study, a strong inflammatory response was observed, as evidenced by markedly increased levels of TNF-α, IL-1β, IL-6, and endotoxin, all of which were positively correlated with the dose of D-gal.…”
Section: Discussionmentioning
confidence: 99%
“…D-gal can cause liver cell necrosis and lead to ALF, as well as abnormally elevated serum TNF-α, which then triggers the cascade of inflammatory mediators and is closely related to the pathophysiology of ALF[ 28 , 29 ]. In our study, a strong inflammatory response was observed, as evidenced by markedly increased levels of TNF-α, IL-1β, IL-6, and endotoxin, all of which were positively correlated with the dose of D-gal.…”
Section: Discussionmentioning
confidence: 99%
“…IMM-H007 or M1 was found to activate cellular AMPK by interacting with the γ subunit, but not by changing the cellular energy state 7 . In our previous study, cordycepin was found to protect against GalN/LPS-induced acute liver failure 11 . Therefore, we speculated that M1 might have the similar beneficial effects on fulminant hepatitis.…”
Section: Introductionmentioning
confidence: 87%
“… 2016 ; Li et al. 2017 ), and mangiferin (Pan et al. 2016 ) can inhibit hepatic injury induced by GalN/LPS.…”
Section: Immunological Liver Injurymentioning
confidence: 99%